A Canonical Correlation Analysis of the Relationship between Income Levels and Resilience to Climate Change - Ernawati, Ernawati (Journal of Business Management and Economic Development, 2025)
This study aims to examine the relationship between economic growth and income level on climate change resilience. An income-level variable is a group of state income consisting of lower, middle, and upper-income countries. Climate change resilience has dimensions of susceptibility, coping capability, and adaptation capacities. This study estimates 174 countries in the 2019 period. Data were obtained from the World Bank and World Risk Report. Data analysis using canonical correlation. The research findings show that the gap between exposure and vulnerability in low-income countries is more prominent than in other groups. Low-income levels have a relationship with low resilience in terms of susceptibility and lack of coping and adaptation capacities. Another finding shows that economic growth is not correlated with resilience to climate change, where economic growth does not automatically reduce vulnerability but only economic growth followed by appropriate policies.